A legitimação de uma identidade masculina por meio de estereótipos femininos constituídos nas/pelas cenografias presentes em propagandas de cerveja - Vaz, Veanney Monod Emidio (2011)
In recent years, whether in print or television to other media outlets in print, has been notorious the presence of a discursive materiality becoming effective and compelling exploration of female sensuality increasingly explicit in beer commercials broadcast by the Brazilian media. Considering this issue, which is presented in this essay, fundamentally based on concepts from the scene of enunciation and discourse deixis, predicted by Dominique Maingueneau in several of his writings is how it is the discourses of publicity advertisements for beer, trying to demonstrate that As the constant presence of a certain female stereotypes in the discourse sceneries of these ads is tantamount / reinforce certain masculine identity. The body of our research consists of 10 billboard advertisements for beer, 5 marks nationally marketed more - Antarctica, Brahma, Skol, Kaiser and Schincariol - which have appeared in advertising campaigns promoted in Brazil over the past 10 years.